Online Module for Acid and Base Topic Based on 5E Model - Shahizah Mahamd Shobri, Nurul Nazatul; Surif, Johari; Ibrahim, Nor Hasniza; Nursiwan, Wimbi Apriwanda; Bunyamin, Muhammad Abd Hadi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Alternative conception or misconception is one of the problems that often be experienced by the students in science subjects including chemistry due to its abstractness and wide scope to be learned. Previous studies found that students often have misconceptions on strength of acid and base topic such as misconception in determining factor that affect the strength of acid and base, differences between strong and weak acid and base as well as the effect of strength of acid and base on conductivity. To overcome these misconceptions, an online teaching and learning module using 5E instructional model was developed. Analysis, Design, Development, Implementation and Evaluation (ADDIE) model is used for research and development. The module used interactive tools and medias to make students being active and understand chemistry well. This module was validated by five experts in term of module objectives, module content, usability, flexibility, learning activities and language aspects with average is ninety percent. The results prove that the module is very good and has high validity. Therefore, the application of online module for acid and base topic based on 5E (Engage, Explore, Explain, Elaborate, Evaluate) model is suitable to be implemented in online teaching and learning process.